Numerical Solution of MHD Boundary Layer Flow of Dusty Fluid Over a Stretching Surface - Lee, Mun Jin; Syahira Mansur, (Enhanced Knowledge in Sciences and Technology, 2024)
This study presents the analysis and discussion of boundary layer flow with dusty fluid. This research discusses the velocity profiles and skin friction coefficient. The effect of the mass concentration of dust particles, fluid particle interaction parameter, and the magnetic field parameter on the velocity profiles. Moreover, the second part were the effect of the mass concentration of dust particles, fluid particle interaction parameter, and the magnetic field parameter on the skin friction coefficient. The governing equations of problems were transformed into nonlinear ordinary differential equations using similarity transformation, which then numerically solved using the RKF45 method in Maple software. The parameters involved were computed, analyzed, and discussed. The velocity profiles is presented graphically while the skin friction coefficient is in tabular form. In addition, a comparison of present skin friction coefficient results with the existing study has achieved excellent agreement. Besides, the magnetic field parameter showed significant effects on the velocity of the fluid and dust particle phases. Furthermore, the skin friction coefficient was increased dramatically as the magnetic field parameter increased.